2013
DOI: 10.1105/tpc.113.113340
|View full text |Cite
|
Sign up to set email alerts
|

ETHYLENE-INSENSITIVE3 Is a Senescence-Associated Gene That Accelerates Age-Dependent Leaf Senescence by Directly Repressing miR164 Transcription in Arabidopsis    

Abstract: Numerous endogenous and environmental signals regulate the intricate and highly orchestrated process of plant senescence. Ethylene is a well-known inducer of senescence, including fruit ripening and flower and leaf senescence. However, the underlying molecular mechanism of ethylene-induced leaf senescence remains to be elucidated. Here, we examine ETHYLENE-INSENSITIVE3 (EIN3), a key transcription factor in ethylene signaling, and find that EIN3 is a functional senescence-associated gene. Constitutive overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
364
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(379 citation statements)
references
References 86 publications
12
364
1
2
Order By: Relevance
“…WRKY53 expression is down-regulated by Whirly1 (Miao et al, 2013), which may explain the coincidence of low transcript levels and high levels of H3K4me3 marks. Examples of posttranscriptional regulation mediated by small RNAs have been identified during leaf senescence (Kim et al, 2009a(Kim et al, , 2009bLi et al, 2013b;Thatcher et al, 2015) and may also explain some of the inconsistencies between H3K4me3 marks and gene expression. Senescence associated gene12 (SAG12), a molecular marker for senescence, was up-regulated 3,300-fold between 29 and 57 d (0.022-72.5 RPKM) and showed increased levels of H3K4me3 marks 250 to 650 bp upstream of the TSS but no clear H3K9ac marks (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY53 expression is down-regulated by Whirly1 (Miao et al, 2013), which may explain the coincidence of low transcript levels and high levels of H3K4me3 marks. Examples of posttranscriptional regulation mediated by small RNAs have been identified during leaf senescence (Kim et al, 2009a(Kim et al, , 2009bLi et al, 2013b;Thatcher et al, 2015) and may also explain some of the inconsistencies between H3K4me3 marks and gene expression. Senescence associated gene12 (SAG12), a molecular marker for senescence, was up-regulated 3,300-fold between 29 and 57 d (0.022-72.5 RPKM) and showed increased levels of H3K4me3 marks 250 to 650 bp upstream of the TSS but no clear H3K9ac marks (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Toward understanding the mechanisms that regulate gene expression during senescence, numerous studies have shown that transcription factors, such as WRKY53 (Hinderhofer and Zentgraf, 2001;Miao et al, 2004;Miao and Zentgraf, 2010), ORESARA1/NAC2 (Oh et al, 1997;Matallana-Ramirez et al, 2013), and ETHYLENE-INSENSITIVE3 (Li et al, 2013b), promote leaf senescence as well as many others listed in the Leaf Senescence Database (Liu et al, 2011). In addition, mutants that affect chromatin structure have been shown to affect senescence; however, phenotypes are often pleiotropic (Lim et al, 2007b;Wu et al, 2008;Ay et al, 2009;Humbeck, 2013).…”
mentioning
confidence: 99%
“…It 226 has been shown that external ethylene stimulates leaf senescence (Bleecker et al, 1988;Zacarias & 227 Reid, 1990), while ethylene-insensitive mutants (etr1-1, ers1, ein2-1, ein2-5, ein3-1 and ein3-1 eil1-1 228 in Arabidopsis and Nr in tomato) show a reduced rate of senescence (Bleecker, 1988;Hua et al, 229 1995;Grbic and Bleecker, 1995;Oh et al, 1997;Lanahan et al, 1994, Li et al, 2013Kim et al, 2014). 230…”
mentioning
confidence: 99%
“…It can activate the expression of NAP (NAM/ATAF1,2/CUC2) and NAC2 (ORE1/NAC092), two 252 important transcription factors controlling leaf senescence Kim et al, 2009;Kim et 253 al., 2014). Furthermore, EIN3 binds to the promotor of the microRNA (miRNA) miR164 and 254 progressively inhibits its expression during leaf development (Li et al, 2013). In turn, miR164 inhibits 255 the expression of the transcription factor NAC2 (Kim et al, 2009;Kim et al, 2014;Li et al, 2013), 256 unraveling a dual feed-forward and feedback regulation of senescence by ethylene through the 257 action of EIN3 ( Figure 1).…”
mentioning
confidence: 99%
“…Both ethylene (ET) and jasmonate (JA) are essential plant hormones that regulate various plant developmental processes and diverse defense responses (Kieber, 1997;Bleecker and Kende, 2000;Guo and Ecker, 2004;Broekaert et al, 2006;Howe and Jander, 2008;Browse, 2009;Shan et al, 2012;Wasternack and Hause, 2013). ET signal is perceived by its receptors ETHYLENE RESPONSE1 (ETR1), ETR2, ETHYLENE RESPONSE SENSOR1 (ERS1), ERS2, and ETHYLENE INSENSITIVE4 (EIN4) (Hua and Meyerowitz, 1998) to repress CONSTITUTIVE TRIPLE RESPONSE1 (CTR1) (Kieber et al, 1993), which activates EIN2 (Alonso et al, 1999;Ju et al, 2012;Qiao et al, 2012;Wen et al, 2012) and subsequently stabilizes EIN3 and EIN3-LIKE1 (EIL1) (Chao et al, 1997;Guo and Ecker, 2003;Potuschak et al, 2003;Gagne et al, 2004) to mediate various ET responses, including hypocotyl growth (Zhong et al, 2012), apical hook formation (Knight et al, 1910;An et al, 2012), root growth (Ortega-Martínez et al, 2007;Růzicka et al, 2007), flowering (Ogawara et al, 2003;Achard et al, 2007), fruit ripening (Burg and Burg, 1962;Theologis et al, 1992), leaf senescence (Gepstein and Thimann, 1981;Li et al, 2013), freezing tolerance , and resistance against pathogen infection (Alonso et al, 2003;Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%